Cystic biliary atresia masquerading as a choledochal cyst - Carolyn Reuland; Clint D. Cappiello (Elsevier, 2021)
Cystic biliary atresia is an uncommon form of biliary atresia that is often misdiagnosed as a choledochal cyst. Here we present a case of a neonate who presented with obstructive jaundice and an antenatally-detected abdominal cyst who was found to have cystic biliary atresia. The patient underwent a successful Kasai procedure for establishment of biliary flow. His initial post-operative course was complicated by three episodes of cholangitis requiring hospital admission. He is now two years out from Kasai portoenterostomy with normal bilirubin levels.